Development and Validation of the Perceived Social Work Competence Scale in China. (January 2017) - Wang, Yean; Chui, Ernest
Objective: This article reports a study that developed and validated the Perceived Social Work Competence Scale (PSWCS) for assessing social work students' competence in Mainland China. Method: The indicators were generated by a broad empirical review of recent literature, confirmed by experts, and indigenized by means of two focus groups of students. Two separate studies were conducted, using samples of social work students. Exploratory factor analyses and reliability tests were conducted on a cross-validation sample ( n 1 = 291) of social work students. Confirmatory factor analyses and tests of predictive validity were conducted on the second sample ( n 2 = 300). Results: The 48-indicator PSWCS (including nine subscales) demonstrated excellent internal consistency, acceptable test–retest reliability, satisfactory factorial validity, and positive correlation with the students' grade point average and their satisfaction with their field experience. Conclusions: The PSWCS is important for enabling students to assess their competence and for enabling educators to improve field education.